Pola Resistensi Bakteri Terhadap Antibiotik Pada Penderita Sepsis Bayi Di Ruang Picu Dan Nicu RSUP Dr. Soeradji Tirtonegoro Klaten Periode Agustus 2013-Agustus 2015 - Maulida, Monica, Prof. Dr. M. Kuswandi, SU., M.Phil., Apt, Ratna Yuliani, M.Biotech.St (2016)
Sepsis is a potentially life-threatening infection, so that early detection is important. The use of antibiotics is still empirically although bacterial resistance patterns changes in each region and time. Therefore, monitoring patterns of bacteria and its sensitivity should be done regularly for the basic selection of antibiotics. The purpose of this study was to determine the highest-causing bacteria and the highest resistance of sepsis-causing bacteria in the Pediatric Intensive Care Unit (PICU) and Neonatal Intensive Care Unit (NICU) Soeradji Tirtonegoro Hospital Klaten during August 2013-August 2015. This study was a non-experimental study with retrospective data collection and analysis of descriptive data. The data were obtained from the culture results and antibiotic sensitivity test. The data of the appropriate of antibiotics use was obtained from the use of antibiotics compared with the sensitivity test results and the antibiotics spectrum activity. Highest sepsis-causing bacteria in the PICU and NICU Soeradji Tirtonegoro Hospital Klaten during August 2013-August 2015 were Pseudomonas sp. (21.81%) and Klebsiella sp. (21.81%). Pseudomonas sp. had high levels of resistance against ampicillin sulbactam (75%), ampicillin (100%), ceftriaxone (25%), cefixime (50%), gentamicin (66.67%), chloramphenicol (16.67%) and cotrimoxazole (25 %). Klebsiella sp. had high levels of resistance against ampicillin sulbactam (83.33%), cefepime (41.66%), meropenem (25%), ampicillin (100%), ceftriaxone (66.67%), cefixime (66.67%), amikacin (8.33%), gentamicin (58.33%), chloramphenicol (16.67%), ciprofloxacin (33.33%) and cotrimoxazole (33.33%). The result of the analysis of appropriateness of antibiotics based on sensitivity test result and bacteria spectrum activity test from sepsis patients in PICU and NICU Soeradji Tirtonegoro Hospital Klaten during August 2013August 2015 showed the percentage of 48,68%. Keywords: resistance, antibiotics, sepsis